Pyloric obstruction due to gastric tuberculosis--an endoscopic diagnosis. - Gupta, B. (BMJ Group, 1990)
A 22 year old male presented with symptoms of gastric outlet obstruction. Endoscopy showed a hypertrophic nodular lesion around the pyloric opening with pyloric stenosis. The endoscopic biopsy and histopathological examination revealed tuberculosis involving the stomach, an extremely rare lesion.